2020
DOI: 10.1016/j.molmet.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic benefits of gastric bypass surgery in the mouse: The role of fecal losses

Abstract: ObjectiveRoux-en-Y gastric surgery (RYGB) promotes a rapid and sustained weight loss and amelioration of glucose control in obese patients. A high number of molecular hypotheses were previously tested using duodenal-jejunal bypass (DJB) performed in various genetic models of mice with knockouts for various hormones or receptors. The data were globally negative or inconsistent. Therefore, the mechanisms remained elusive. Intestinal gluconeogenesis is a gut function that has been suggested to contribute to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Various studies have confirmed that SCFAs participate in the regulation of NAFLD by activating G-protein-coupled receptor (GPR) 41 or 43, which are expressed in various areas, such as adipose, liver, tissues, peripheral blood, and intestinal cells ( 47 , 48 ). As per previous publications, intestinal gluconeogenesis (IGN) functions as a regulator of NAFLD via upregulation of hepatic insulin sensitivity and downregulation of hepatic glucose production (HGP) through the gut-brain-liver neural circuit ( 49 , 50 ).…”
Section: Gut Microbiota and Short Chain Fatty Acidsmentioning
confidence: 80%
“…Various studies have confirmed that SCFAs participate in the regulation of NAFLD by activating G-protein-coupled receptor (GPR) 41 or 43, which are expressed in various areas, such as adipose, liver, tissues, peripheral blood, and intestinal cells ( 47 , 48 ). As per previous publications, intestinal gluconeogenesis (IGN) functions as a regulator of NAFLD via upregulation of hepatic insulin sensitivity and downregulation of hepatic glucose production (HGP) through the gut-brain-liver neural circuit ( 49 , 50 ).…”
Section: Gut Microbiota and Short Chain Fatty Acidsmentioning
confidence: 80%
“…SCFAs act as important sources of nutrients and energy from the intestinal epithelium, which is critical for the maintenance of the intestinal homeostasis. SCFAs were demonstrated by a variety of studies to participate in the regulation of NAFLD by activating G-protein-coupled receptor (GPR)­41 or/and 43, which is expressed in the adipose, intestinal, liver, peripheral blood, or nervous tissues. , As reported, intestinal gluconeogenesis (IGN) functions as a regulator of the setup of NAFLD evidenced by an increase in hepatic insulin sensitivity and a decrease in HGP through a gut–brain–liver neural circuit, and it can be triggered by some beneficial macronutrients. , Interestingly, SCFAs, including propionate and butyrate, can induce IGN during the presence of de novo -synthesized glucose from the gut epithelium, which initiates the glucose signal to the brain via a GPR41-mediated neural circuit mechanism, thereby increasing insulin sensitivity and glucose tolerance. In addition to activation of the GPR, SCFAs can directly enter the liver through the portal vein where they improve hepatic glycolipids homeostasis via the activation of AMPK in a peroxisome proliferators-activated receptors (PPAR)­γ-dependent manner . Emerging research has also implicated that SCFAs can travel across the blood–brain barrier (BBB) into CNS and affect the cellular biological mechanism of the neural development (microglia, BBB permeability, neurogenesis), thereby resulting in various physiological processes of the liver, including gluconeogenesis, insulin sensitivity, and AMPK activity. , The above evidence indicates that SCFAs acts as an important signaling molecule used for communication between the microbiota and the host tissues via the gut–brain–liver axis.…”
Section: Regulation Of Gut Microbiota-derived Metabolitesmentioning
confidence: 98%
“…89,90 As reported, intestinal gluconeogenesis (IGN) functions as a regulator of the setup of NAFLD evidenced by an increase in hepatic insulin sensitivity and a decrease in HGP through a gut−brain−liver neural circuit, and it can be triggered by some beneficial macronutrients. 91,92 Interestingly, SCFAs, including propionate and butyrate, can induce IGN during the presence of de novo-synthesized glucose from the gut epithelium, which initiates the glucose signal to the brain via a GPR41-mediated neural circuit mechanism, thereby increasing insulin sensitivity and glucose tolerance. 93−95 In addition to activation of the GPR, SCFAs can directly enter the liver through the portal vein where they improve hepatic glycolipids homeostasis via the activation of AMPK in a peroxisome proliferators-activated receptors (PPAR)γ-dependent manner.…”
Section: ■ Adjustment Of Intestinal Microbiotamentioning
confidence: 99%
“…Many of these mechanisms are also linked to T2DM and CV risk (Table 3). These include increased insulin sensitivity [36,39], decreased insulinlike growth factor (IGF)-1 [37], altered intestinal bile acid concentration [45], decreased adipose tissue and systemic inflammation (with lower levels of circulating inflammatory cytokines) [36,52], a favorably altered gut microbiome [43,46] and epigenetic changes [42], decreased adipocyte size [41] (which allows more normal adipocyte functioning), decreased aromatase production [44] and enzymatic conversion of androgens to estrogen [36] thereby limiting the increase in circulating estrogen, lowering oxidative stress [38], and increasing intestinal gluconeogenesis [10,40]. Some of these proposed mechanisms are supported by MBS animal studies, as we outline in in Section 3.…”
Section: Proposed Mechanisms Leading To Cancer Risk Reduction After Mbsmentioning
confidence: 99%